Monitoring System Indoor Mushroom Cultivation via Telegram Bot - Sandikyawan, Rio Ridho; Arifin, Samsul (Journal of Informatics Development, 2024)
Mushroom cultivation in Indonesia has significant potential due to its tropical climate, which is ideal for growing various types of mushrooms. However, maintaining optimal environmental conditions, such as temperature and humidity, is crucial for successful cultivation. This study aims to design and develop an Internet of Things (IoT)-based monitoring system for indoor mushroom farming, utilizing NodeMCU and Telegram Bot for real-time data management. IoT is used in mushroom cultivation to monitor and manage environmental conditions in real-time, considering that mushroom growth is very sensitive to changes in temperature and humidity. The main challenges faced are ensuring the stability of environmental conditions and reducing communication delays in data transmission to maintain the quality and quantity of mushroom production. The system employs a DHT11 sensor connected to a NodeMCU 8266 microcontroller to monitor temperature and humidity. Data is transmitted to farmers via the Telegram app, allowing for remote monitoring and early warning alerts when environmental parameters exceed safe limits. Field testing and performance evaluations were conducted, comparing mushroom growth between crops cultivated with and without the monitoring system. The results show that mushrooms grown under the IoT-based system achieved better growth, with the system maintaining optimal conditions between 24°C to 27°C for temperature and 80% to 90% for humidity. Communication delays averaged 9 seconds, which impacted the successful rate of real-time monitoring. Overall, the system improved the control of environmental conditions and supported enhanced mushroom growth, demonstrating its effectiveness in optimizing cultivation practices. transmission rates and maintaining environmental parameters to further improve cultivation results.